Hermitian–Toeplitz and Hankel determinants for Sakaguchi-type functions defined by a rational function - Buyankara, Mucahit; Çağlar, Murat (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We obtain the best possible estimates for the Hermitian–Toeplitz determinant of the third order for a class of starlike functions with respect to a symmetric point associated with a rational function. In addition, we determine the upper bounds for the third Hankel determinants.